Dadaji Bhikaji v Rukhmabai (1886) ILR 10 Bom 301: rewriting consent and conjugal relations in colonial India. Issue 3 (2nd September 2021) - Sharma, Kanika; Lammasniemi, Laura; Sarkar, Tanika
ABSTRACT: Through an examination of the late nineteenth century case of Dadaji Bhikaji v Rukhmabai this article traces the history of the doctrine of restitution of conjugal rights ("RCR") in Hindu law in colonial India. It highlights the importance of caste in situating the life and trials of Rukhmabai in their wider social, colonial, and legal contexts. Following the methodology of the global feminist judgements projects, the paper also offers a re-written judgement for Rukhmabai's case located in 1886. This new judgement, while bound by the legal rules of the time, puts forward an alternative application of the doctrine of RCR, one that treats the issue of consent as central to such suits. It argues that the legal transplant of RCR ought not to have been applied to Hindu marriages which are often entered into in childhood and makes a case for taking into account female consent to both marriage and to conjugal relations.